(untitled) (International Journal of Innovative Technologies in Economy, 2021)
The article is devoted to the substantiation of scientific and theoretical provisions and recommendations for the improvement of accounting and analytical procedures for the formation of reserves at an agricultural enterprise to ensure the reliability of determining the financial results of their activities. The methodological approach to the formation of reserves in the traditional models of accounting in agricultural enterprises is analyzed. Generalized concepts of formation and use of reserves in national regulations (standards) of accounting and international standards of financial reporting. The conceptual direction in accounting provides economic information on costs, which is used in management functions, namely in planning, analysis, control, regulation, incentives, justification of decisions on strategic development and financial and economic security. Documentary provision of the reserve of vacations and the reserve of doubtful debts, the use of which is a priority of effective stable activity and management of the enterprise, is offered. The prepayment document is an alternative primary document for the correct calculation and generalization of the amount of the reserve at the agricultural enterprise.